(Invited) The Effect of Dopants on the Stabilization of the Cubic BSCF Phase in O2- and CO2-Containing Atmospheres. (3rd May 2017) - Gerthsen, Dagmar; Meffert, Matthias; Störmer, Heike; Wilde, Virginia; Almar, Laura; Sigloch, Fabian; Unger, Lana-Simone; Wagner, Stefan F.; Ivers-Tiffée, Ellen
Abstract : The effect of Y-, Nb- and Ti-doping on the stability of the cubic (Ba0.5 Sr0.5 )(Co0.8 Fe0.2 )O3- d (c-BSCF) phase in O2 - and CO2 -containing atmospheres was studied in a temperature range between 640 and 880 °C. Electron microscopy investigations demonstrate that secondary phase formation in 10 at% Y-doped BSCF (BSCF10Y) is almost completely suppressed and XRD analyses on powders also show improved stability for 10 at% Nb- and Ti-doped BSCF. Furthermore, electrochemical impedance spectroscopy measurements of symmetrical cells in CO2 -containing atmospheres show significantly less poisoning effect on oxygen reduction reaction for BSCF10Y compared to undoped BSCF cathodes, while the latter developed a high density of small precipitates on the surface after exposure to CO2 .